Recent agroclimatic maps of temperature, frost and rainfall in La Pampa (Argentina) (Semiárida, 2020)
Agricultural production implies the management of a set of physical, biological and economic systems. The uncertainties of these systems contribute to the complexity of decision making and reduce the efficiency of agricultural management. Knowledge about the climatic environment in which plants and animals develop can produce progressive increases of production levels and more efficient productive processes. Mapping is one of the tools required for decision making in the multiple environmental problems related to agricultural planning, and in this particular case a representation of regional agrimeteorological information. The present study is the actualization of isolines for average annual temperature, and for the coldest and warmest month, frost occurrence and annual rainfall in La Pampa, in order to contribute to the knowledge about their behavior.
Keywords: La Pampa; isolines; temperature; frost; rainfall